Religion's Role in Mitigating Social Conflicts in Rural Communities: Insights from a Case Study in Indonesia - Dody S. Truna; Ahmad Gibson Albustomi (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
This study investigates the role of religion in managing social conflict in rural areas, focusing on the practice of the musyawarah forum in Cimaung, Bandung Regency. Religion is conceptualized not merely as a symbol but as an epistemological framework and symbolic capital that provides social legitimacy in mediation processes. Employing a qualitative approach, this research combined participant observation, in-depth interviews, and NVivo-assisted analysis to capture discursive patterns within the forum’s practices. The findings reveal that religious leaders act as insider mediators, whose moral legitimacy enables them to effectively bridge communal disputes. Qur’anic values such as shura (consultation), rahmah (compassion), afw (forgiveness), and ‘adl (justice) constitute the forum’s foundation, thereby producing forms of positive peace that transcend immediate conflict resolution and foster long-term social cohesion. Challenges faced by the forum include the politicization of religious identity and heavy reliance on charismatic leaders. Practically, this study recommends strengthening the institutional capacity of religious-based forums to ensure inclusivity, sustainability, and resilience in rural peacebuilding. Contribution: This study contributes to the global discourse on religious peacebuilding by providing empirical evidence from rural Indonesia, offering a Qur’an-based musyawarah model as a grassroots peace infrastructure relevant to international debates.